Evaluasi Praktik Meritokrasi dalam Kebijakan Publik di Indonesia: Pendekatan Bibliometrik dan Psikometrik - Rahmad Hidayat; Nurillah Agustina; M. Ariy Dermawan (UNIVERSITAS ISLAM SYEKH YUSUF, 2025)
The principle of meritocracy is an important foundation for professional, accountable, and integrity-based governance. However, in the Indonesian context, the implementation of this principle still faces various challenges, both structurally, culturally, and institutionally. Although the bureaucratic reform agenda has been rolled out, the integration of meritocracy into public policy has not been optimal. Therefore, a systematic study is needed to evaluate the practice of meritocracy in order to identify achievements, obstacles, and opportunities for strengthening merit-based policies. This study aims to evaluate the practice of meritocracy in public policy in Indonesia through a Systematic Literature Review (SLR) approach combined with bibliometric and psychometric analysis. This study reviews various research results from 2015-2024 obtained from the Scopus and Dimensions databases. Selection was based on publication quality, topic relevance, and full-text availability in Indonesian and English. The study results show a thematic focus on bureaucratic reform, public human resource management, and performance-based governance. Bibliometric mapping shows that meritocracy research is still scattered and has not been optimally integrated across sectors. Psychometric approaches are also rarely used, especially in developing instruments for measuring perceptions and practices of merit at the organizational and individual levels. The study's conclusions emphasize the importance of strengthening meritocracy through a multidimensional evaluative approach. Psychometric instruments are needed that are contextual and sensitive to the culture of public organizations in Indonesia. Furthermore, cross-disciplinary collaboration, the use of information technology, and consistent institutional reform are prerequisites for realizing effective meritocratic policies. These findings are expected to form the basis for formulating more adaptive and justice-oriented public policies and improving public service performance.